Precision-cut kidney slices (PCKS) to study development of renal fibrosis and efficacy of drug targeting ex vivo - Fariba Poosti; Bao Tung Pham; Dorenda Oosterhuis; Klaas Poelstra; Harry van Goor; Peter Olinga; Jan-Luuk Hillebrands (Disease Models & Mechanisms, 2015)
Renal fibrosis is a serious clinical problem resulting in the greatest need for renal replacement therapy. No adequate preventive or curative therapy is available that could be clinically used to target renal fibrosis specifically. The search for new efficacious treatment strategies is therefore warranted. Although in vitro models using homogeneous cell populations have contributed to the understanding of the pathogenetic mechanisms involved in renal fibrosis, these models poorly mimic the complex in vivo milieu. Therefore, we here evaluated a precision-cut kidney slice (PCKS) model as a new, multicellular ex vivo model to study the development of fibrosis and its prevention using anti-fibrotic compounds. Precision-cut slices (200-300 μm thickness) were prepared from healthy C57BL/6 mouse kidneys using a Krumdieck tissue slicer. To induce changes mimicking the fibrotic process, slices were incubated with TGFβ1 (5 ng/ml) for 48 h in the presence or absence of the anti-fibrotic cytokine IFNγ (1 µg/ml) or an IFNγ conjugate targeted to PDGFRβ (PPB-PEG-IFNγ). Following culture, tissue viability (ATP-content) and expression of α-SMA, fibronectin, collagen I and collagen III were determined using real-time PCR and immunohistochemistry. Slices remained viable up to 72 h of incubation, and no significant effects of TGFβ1 and IFNγ on viability were observed. TGFβ1 markedly increased α-SMA, fibronectin and collagen I mRNA and protein expression levels. IFNγ and PPB-PEG-IFNγ significantly reduced TGFβ1-induced fibronectin, collagen I and collagen III mRNA expression, which was confirmed by immunohistochemistry. The PKCS model is a novel tool to test the pathophysiology of fibrosis and to screen the efficacy of anti-fibrotic drugs ex vivo in a multicellular and pro-fibrotic milieu. A major advantage of the slice model is that it can be used not only for animal but also for (fibrotic) human kidney tissue.